2009
DOI: 10.1142/s0218488509006248
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Cognitive Structure of Uncertain Scientific Concepts Using Fuzzy-Rough Sets and Intuitionistic Fuzzy Sets: Example of the Life Concept

Abstract: In this study, using fuzzy-rough set and intuitionistic fuzzy set approaches, we propose a cognitive structural model for the concept of life for which a certain definition can not be made because of scientific uncertainty as well as moral, legal, and theological aspects. Total 191 first-year students from seven different high schools in a large western city in Turkey participated in the study. An open-ended conceptual understanding (CULC) test, developed by the researcher, was used for data collection. Semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Starting from the fact that human and animals stand out considerably in this study, we suggest an animisticanthropocentric conceptual construction model about the life concept (Figure 1). In constructing this model we have represented the life and related concepts and sub-concepts with circles (Yorek & Narli, 2009).…”
Section: Animistic-anthropocentric Construction Model Of the Life Conmentioning
confidence: 99%
“…Starting from the fact that human and animals stand out considerably in this study, we suggest an animisticanthropocentric conceptual construction model about the life concept (Figure 1). In constructing this model we have represented the life and related concepts and sub-concepts with circles (Yorek & Narli, 2009).…”
Section: Animistic-anthropocentric Construction Model Of the Life Conmentioning
confidence: 99%
“…According to our literature survey, it was observed that the cognitive construction of aliveness concept was closely associated with anthropocentrism and animism [ 13 19 , 22 , 24 , 31 , 32 , 39 , 55 ]. The results obtained from this study appeared to be consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Yorek et al [ 24 ] have questioned whether there can be a distinction among living creatures due to aliveness based on “animistic-anthropocentric model” they have developed. In another study, which uses the same model, subject was evaluated with fuzzy and rough set approaches and a mathematical model was suggested [ 39 ]. We initiated this study with the question “How can we use SOMs in analyzing and visualizing cognitive structure of aliveness concept?” with the motivation of the idea of so called mathematical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, rough set analysis is added to the tools, which includes regression analysis and Bayes' Theorem, for pattern recognition and feature selection in data mining, see [19,36,10,37,29,5,26,28]. The resulting applications include in medical databases [32,31,30,8,9,12,13], cognitive science [16,14,25,17,35], artificial intelligence and machine learning [15,11,7,6,33,21,27] and engineering [1,2,3,24,23]. Indeed in [34], Yao noted that there is currently an imbalance in the literature between the conceptual unfolding of rough set theory and its practical computational progress.…”
Section: Successive Approximationsmentioning
confidence: 99%